Inhaled Nitric Oxide as an Adjunct to Thrombolytic Therapy in a Patient with Submassive Pulmonary Embolism and Severe Hypoxemia - Omesh Toolsie; Umut Gomceli; Gilda Diaz-Fuentes (Case Reports in Critical Care)
Introduction. Inhaled nitric oxide (iNO) is a selective pulmonary vasodilator with limited indications in adults. We present a patient with hypoxemia and right ventricular dysfunction due to submassive acute pulmonary emboli where iNO was used as a bridge to thrombolysis. Case. A 29-year-old male was admitted to the intensive care unit (ICU) for alcohol intoxication complicated with aspiration pneumonia and acute respiratory failure requiring mechanical ventilation. His medical history included morbid obesity (BMI 43) and alcohol dependence syndrome. Nine days after admission, he developed severe acute hypoxia and tachycardia with arterial oxygen tension (PaO2) of 52 mmHg requiring a positive end-expiratory pressure (PEEP) of 14 cmH2O and fraction of inspired oxygen (FiO2) of 1. Chest computed tomography (CT) revealed a large embolus in the right main pulmonary artery and transthoracic echocardiogram (TTE) reported new right ventricular dilatation with decreased right ventricular function. Due to the severe hypoxemia, he was started on iNO via the breathing circuit of the ventilator at a concentration of 20 parts per million (ppm) with steady improvement in oxygenation after 1 hour with a PaO2 of 81 mmHg on the same ventilator setting. The patient was given thrombolysis with alteplase and the iNO was slowly tapered off during the subsequent four days with concomitant successful tapering of PEEP to 8 cmH2O and FiO2 of 0.45. Conclusion. Inhaled NO has been used to improve ventilation-perfusion matching and also to reduce pulmonary vascular resistance (PVR). Its effects on PVR may be useful in the setting of acute pulmonary emboli where vascular obstruction and vasoconstriction contribute to increased pulmonary arterial pressure and PVR which can present as acute right heart failure. We suggest that iNO, if available, could be considered in those patients with acute pulmonary emboli associated with significant hypoxemia as an adjunctive therapy or bridge to thrombolysis or thrombectomy.